ANALISIS KERJASAMA PEMERINTAH DAERAH DKI JAKARTA DENGAN YAYASAN DHARMARANYA TUJU ENAM DALAM PEMBANGUNAN TAMAN PINTAR PULOGADUNG - Dhimas Andisca; Priyatno Harsasto; Muhammad Adnan (Journal of Politic and Government Studies, 2016)
This research is based on building growth in Jakarta City which is more increasing, this makes Jakarta City more loses its green area that this time experiences quality degradation in its environment. The building in Jakarta area has to place RTH as a backbone of city building in decreasing flood (water absorbing area), absorbing pollutant and supplying oxygen (city lungs). For optimalizing RTH building, Pemda DKI Jakarta has to add the total of RTH which kinds like interactive garden. Pemda DKI Jakarta interlaces cooperation with Dharmaranya Tuju Enam Foundation in building outdoor green area in Smart Garden in Warigin Raya St. No. 25/Gereja St. Kayu Putih Village, Pulo Gadung Sub-district, East Jakarta. Type of this research is descriptive analytical through qualitative approach. Sources are found from primary data that is through interviewing he informant or key person by Purposive Sampling technique. Meanwhile, the secondary data comes from documents, archieves and other sources which relate to this research. Data collection technique in this research uses interview, observation and documentation.Result of research’s found that cooperation between Pemda DKI Jakarta and YDTE based on Governor Decision No. 2 of 2002 about Manual Implementation of Miter Cooperation in Garden Affair Sector DKI Jakarta Province and Miter Program of 2008. Cooperation whis is interlaced between Pemda DKI Jakarta and YDTE is a cooperation in the form of BOT (Build, Operate, Transfer), that is cooperation is implemented by the way that private side which build Smart Garden, operating this gardenand then giving back to government after the ending of the contract, that is 5 months. There is 3 principles which become the basic of this cooperation, there are: equality, transparancy and the principle of mutual benefit. By using those principles, the more effective and comfortable cooperation pattern has created between Pemda DKI and YDTE which all this time run smooth and good based on the treaty which is agreed.